Pengaruh Seleksi Dan Pendidikan Terhadap Perekrutan Karyawan Pt. Ingco Teknika Indonesia Medan - Khaterine Pratama; Syawaluddin Syawaluddin; Aidil Putra; Thomas Sumarsan Goh (YUME : Journal of Management, 2022)
Abstrak Recruitment activities are very important to find new potential employees who have potential in the company. Given the very importance of the recruitment process for the company, it is hoped that a selective selection process will have an impact on the company's future development to obtain quality resources. Some employees of PT. IngcoTeknika Indonesia Medan whose education is not linear and even too far related to the position occupied at this time. The low level of employee education can be proven by the last formal education that the employee has taken. The purpose of this study was to determine the effect of selection and education on the recruitment of PT. IngcoTeknika Indonesia Medan. The research method used is a survey approach analysis method, the type of research is quantitative descriptive, the research method is carried out by questionnaires, interviews, and documentation studies. The analytical method used is multiple linear regression. The population is employees of PT. IngcoTeknika Indonesia Medan. The sample in the study to be tested is 35 people. The data analysis technique used is the reliability validity test, the classical assumption test, the coefficient of determination (R2) test, multiple regression analysis, and hypothesis testing. Keywords: Selection, Education, Employee Recruitment